2023
DOI: 10.1021/acsnano.2c10687
|View full text |Cite
|
Sign up to set email alerts
|

Robust Helical Dichroism on Microadditively Manufactured Copper Helices via Photonic Orbital Angular Momentum

Abstract: Three-dimensional chiral metallic metamaterials have already attracted extensive attention in the wide research fields of chiroptical responses. These artificial chiral micronanostructures, possessing strong chiroptical signals, show huge significance in next-generation photonic devices and chiroptical spectroscopy techniques. However, most of the existing chiral metallic metamaterials are designed for generating chiroptical signals dependent on photonic spin angular momentum (SAM). The chiral metallic metamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…[670] The field of TPL printing related topological photonics and BIC related photonics is still newborn, but rapidly growing with cutting-edge physical concepts. [671][672][673][674] It is expected that the burgeon of topological or BIC photonics will rely more on the TPL based fabrication techniques. bound states in the continuum.…”
Section: Topological Opticsmentioning
confidence: 99%
“…[670] The field of TPL printing related topological photonics and BIC related photonics is still newborn, but rapidly growing with cutting-edge physical concepts. [671][672][673][674] It is expected that the burgeon of topological or BIC photonics will rely more on the TPL based fabrication techniques. bound states in the continuum.…”
Section: Topological Opticsmentioning
confidence: 99%
“…Recently, ultra-fast laser direct writing, with good consistency and a negligible heat-affected zone, has been widely utilized to control the surface wettability and topography. [18][19][20][21][22][23] Numerous efforts have been devoted to laser processing for achieving efficient solar desalination. For example, Yin et al reported a femtosecond laser structured foam titanium used for solar desalination.…”
Section: Introductionmentioning
confidence: 99%
“…Light field with orbital angular momentum (OAM) is also known as vortex beam which has been well applied in optical tweezers, [12] communication, [13] manufacturing, [14] etc. [15,16] The helical wavefront also gives vortex beam a chiral degree of freedom and its handedness is determined by the sign of the OAM munber l. [17][18][19] Interestingly, recent theoretical and experimental studies have demonstrated that the interaction between vortex beam and chiral matters depends on the sign of l. [20][21][22][23][24][25][26][27][28][29][30] This suggests that photonic OAM can provide another promising approach to investigate chiral physics. The giant helical dichroism (HD) has been achieved for a single helix, [25,29] planar-chiral nanostructure, [26] twisted stereometamaterial, [27] and chiral oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] The helical wavefront also gives vortex beam a chiral degree of freedom and its handedness is determined by the sign of the OAM munber l. [17][18][19] Interestingly, recent theoretical and experimental studies have demonstrated that the interaction between vortex beam and chiral matters depends on the sign of l. [20][21][22][23][24][25][26][27][28][29][30] This suggests that photonic OAM can provide another promising approach to investigate chiral physics. The giant helical dichroism (HD) has been achieved for a single helix, [25,29] planar-chiral nanostructure, [26] twisted stereometamaterial, [27] and chiral oligomer. [28] With the virtues of HD spectroscopy, enantiomeric distinction can be performed using monochromatic linearly polarized light fields, which is completely different from circular dichroism spectroscopy methods.…”
Section: Introductionmentioning
confidence: 99%